Inexpensive multi-plane particle image velocimetry based on defocusing: proof of concept on two-component measurement - He, Q; Willman, C; Stone, CR; Williams, B (AIP Publishing, 2023)
This paper presents a method for simultaneous particle image velocimetry (PIV) on parallel planes offset in depth. The method places images from two planes onto a different half of a camera sensor by using image splitting optics with variable optical path lengths. A shallow depth of field is achieved to ensure only one plane is in focus on each half of the sensor. Without needing additional lasers, the method is designed as an inexpensive means to increase the number of measurement plane(s) of single/multi-plane PIV setups and can be combined with existing plane discrimination approaches such as polarization and wavelength. The method is useful for studying instantaneous flow correlations on different planes while retaining high in-plane spatial resolution of typical planar PIV measurement. The measurement uncertainty caused by crosstalk from out-of-focus images is discussed. Experimental results from a laminar flow rig test indicate that the average measurement error of each velocity component is lower than 0.1 pixels per time step, with a 20 mm plane separation in depth and a 35 × 54 mm2 field of view. As an application with varying background scatter and out-of-plane flow motions, in-cylinder flow measurements in an optically accessible internal combustion engine were performed on two swirl planes simultaneously. Characteristics of the proposed method performing stereoscopic PIV measurements will be studied in future.